Unmet need for family planning and related difficulties among married women of childbearing age in Bandung Slum, Indonesia - Asti Dewi Rahayu Fitrianingsih; Ema Novita Deniati (AOSIS, 2022)
This study was conducted to assess what factors cause women of childbearing age (15-49 years) who live in slums in Bandung City, Indonesia to experience unmet need for family planning. Unmet need for family planning is a phenomenon in the population sector that requires serious and immediate treatment because it can inhibit the increase in Contraceptive Prevalence Rate (CPR) and decrease in Total Fertility Rate (TFR). A cross-sectional survey was conducted from February to July 2021. 304 women were selected as respondents using a purposive sampling technique. Univariate and multivariate regression analysis was performed using STATA 16. The result is 29.3% of women have unmet need for family planning, while the factors that influence the occurrence of unmet need for family planning include marital age, family income, experienced a child's death, number of children living, women's decision-making power, and media exposure. Increasing access to information and free family planning services for married couples is important, especially for low-income families with many children.